Road traffic noise in areas surrounding intersections - Motylewicz, Marek; Gardziejczyk, Władysław (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
Over the period of the last few years special attention has been paid to the issue of protecting built-up areas against excessive traffic noise. Prediction and assessment of the level of noise in areas surrounding intersections was of primary interest to the researchers. Studies in this field have been carried out in numerous research centers in Poland and around the world. Existing noise prediction models describe the noise level in areas close to intersections with different degree of accuracy, depending on the number and type of factors included in the model. The paper presents the results of studies on the equivalent noise level in the surroundings of various types of intersections. It shows the impact of the following factors on traffic noise: geometry, traffic organization, traffic composition and distribution as well as the distance from the intersection. It was stated that apart from the basic traffic parameters (intensity and composition) and the characteristics of entries, some factors, including intersection geometry, organization and management of traffic and the traffic conditions should be analysed in greater detail.